2005
DOI: 10.1111/j.1523-1739.2005.00245.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Immigration in the Decline of an Isolated Migratory Bird Population

Abstract: Low immigration is rarely considered a potential causal factor in the population decline of migratory birds. Because migratory songbirds exhibit low natal philopatry, however, recruitment is from outside the population. Therefore, if isolation affects immigration the geographic fragmentation of a species' range may result in population declines. I tested four hypotheses on the possible causes of population decline of an isolated population of Yellow‐headed Blackbirds (Xanthocephalus xanthocephalus) in Illinois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 50 publications
3
45
0
Order By: Relevance
“…While there are no comparable data on apparent survival in Yellow-breasted Chats elsewhere, the apparent survival rate of 65% (66% combined) for male Western Yellow-breasted Chats in the southern Okanagan valley was at the high end of the range of 43%-70% for survival rates for long-term studies of migratory songbirds (e.g., Budnik et al 2000;Bayne and Hobson 2002;Jones et al 2004;Ward 2005;Fletcher et al 2006;Schlossberg 2009;Cox and Jones 2010). Return rate in the Okanagan for adult male chats was 44% and apparent survival was 65%, which is still a minimum survival estimate because it does not account for males that could have survived but dispersed outside of the study area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While there are no comparable data on apparent survival in Yellow-breasted Chats elsewhere, the apparent survival rate of 65% (66% combined) for male Western Yellow-breasted Chats in the southern Okanagan valley was at the high end of the range of 43%-70% for survival rates for long-term studies of migratory songbirds (e.g., Budnik et al 2000;Bayne and Hobson 2002;Jones et al 2004;Ward 2005;Fletcher et al 2006;Schlossberg 2009;Cox and Jones 2010). Return rate in the Okanagan for adult male chats was 44% and apparent survival was 65%, which is still a minimum survival estimate because it does not account for males that could have survived but dispersed outside of the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Our natal philopatry in the south Okanagan of 10.1% falls at the high end of the range of typical rates (0%-16%) for long-term studies of North American migratory species (e.g., DiQuinzio et al 2001;Sedgwick 2004;Schlossberg 2009;Ward 2005). None of the Eastern Yellow-breasted Chat nestlings banded in Indiana returned to their natal site in subsequent years (Thompson and Nolan 1973).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that females select wetlands based on odonate emergence (Orians and Wittenberger 1991). The species is also known to have high brood reduction (Forbes et al 2002;MP.Ward, unpublished data), with the amount of food at a site correlated with the number of young fledged (Orians 1980;Ward 2004). Therefore, if yellow-headed blackbirds could assess the relative odonate emergence at a site it may provide a valuable cue in habitat selection.…”
Section: Introductionmentioning
confidence: 95%
“…I chose to investigate the role of food availability, density, and the number of young per female because all three cues may provide valuable information that could be used in the habitat selection process. Yellow-headed blackbirds are known to primarily feed their young emerging insects of the order Odonata i.e, dragonflies and damselflies (Orians 1966(Orians , 1980Willson 1966;Orians and Horn 1969;Ward 2004). It has been suggested that females select wetlands based on odonate emergence (Orians and Wittenberger 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing awareness of the role of immigration in driving population Xuctuations in a range of bird species (Hitchcock and Gratto-Trevor 1997;Ward 2005;Lampila et al 2006). In relation to understanding climate eVects, this makes it diYcult to produce a complete demographic model for a particular population, because of the uncertainty regarding factors that may aVect productivity in other, unstudied populations, or the tendency for immigrants to settle within a particular area.…”
Section: Discussionmentioning
confidence: 99%